Childhood trauma and cardiometabolic risk in severe mental disorders: The mediating role of cognitive control. Issue 1 (29th March 2021) - Lunding, Synve Hoffart; Simonsen, Carmen; Aas, Monica; Rødevand, Linn; Werner, Maren Caroline Frogner; Laskemoen, Jannicke Fjæra; Hjell, Gabriela; Ringen, Petter Andreas; Lagerberg, Trine Vik; Melle, Ingrid; Andreassen, Ole A.; Ueland, Torill; et al.
Abstract: Background: Cardiometabolic risk is increased in severe mental disorders (SMDs), and there appears to be a relationship between childhood trauma and cardiometabolic risk, possibly related to adverse health behavior. The current study examined the association between childhood trauma and serum lipids and adiposity in SMDs and the potential mediating role of cognitive and personality characteristics. Methods: Participants with schizophrenia and bipolar spectrum disorders ( N = 819) were included, cardiometabolic risk factors ( serum lipids, body mass index, and waist circumference) were measured, and history of childhood trauma was assessed by the Childhood Trauma Questionnaire. Cognitive and personality characteristics were available in subsamples, with assessments of cognitive control, impulsiveness, self-esteem, and affective lability. Linear regressions and mediation analyses with Hayes' PROCESS were performed, adjusting for age, sex, antipsychotic agent propensity of metabolic side-effect, and diagnostic group. Results: Experience of three or more subtypes of childhood trauma was positively associated with waist circumference in patients with SMDs ( p = 0.014). There were no other significant associations between trauma variables and lipid or adiposity measures in the total sample. Cognitive control was a significant mediator between experience of one or two subtypes of childhood trauma and waist circumference. Conclusions: The results indicate childhood trauma as a predisposing factor for increased waist circumference in individuals with SMDs. Poorer cognitive control, suggestive of adverse health behavior, might be a mediating factor of the association, and the findings indicate the potential importance of increased focus on these factors in prevention and treatment regimens targeting cardiometabolic health.